Nasal trigeminal projections and medullary dorsal horn neuronal activation during voluntary diving in rats - McCulloch, P. F.; Margosiak, M.; Namburi, H.; Kernosek, K.; DiNovo, K. M. (Frontiers in Physiology, 2025)
The diving response, an autonomic reflex characterized by apnea, bradycardia and increased peripheral vascular resistance, is initiated when animals submerge underwater. Neurons located within the trigeminal nucleus caudalis, specifically the ventral medullary dorsal horn (MDH), become activated and produce Fos after repetitive diving. It is assumed nerves innervating the nasal passages are important for activating these neurons during diving. The present study investigated the anatomical route by which nasal stimulation during diving can produce activation of MDH neurons. In rats trained to repetitively dive underwater, transganglionic tracer WGA was injected into the nasal passages or nerves innervating the nasal passages. Immunohistochemistry revealed the ventral superficial laminae of the MDH, between the pyramidal decussation and obex, receives central terminations from the nasal passages, superimposing the location containing neurons activated by repetitive diving. After WGA injection into the nasal passages, colocalization of WGA and Fos-positive neurons increased significantly from 4.6 ± 2.1 in non-diving rats to 32.3 ± 10.6 in diving rats. After WGA injection into the anterior ethmoidal nerve (AEN), colocalization of WGA and Fos-positive neurons increased significantly from 10.3 ± 3.2 in non-diving rats to 29.0 ± 5.2 in diving rats. Additionally, diving rats exhale air bubbles from their nose during diving and allow water to enter their nasal passages while underwater. We conclude sensory information projecting from the nasal passages via the AEN likely activates MDH neurons and induces them to produce Fos during repetitive diving. We are less confident about the role of the nasopalatine nerve.